HUBUNGAN INTENSITAS KOMUNIKASI ANTAR PRIBADI MENTOR – MURID DAN INTERAKSI DENGAN KELOMPOK DALAM GEREJA DENGAN MINAT MURID UNTUK TERLIBAT AKTIF SEBAGAI ANGGOTA PELAYANAN DI ORGANISASI GEREJA GBI GAJAH MADA SEMARANG - Junelsa Panggalo; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research aims to determine the correlation of the intensity of interpersonal communication of discipler – disciple and the interaction with groups in the church with disciple’s interest to be actively involved as a member of ministry in GBI Gajah Mada Semarang church organization. The Theory of Reasoned Action and Learning Social Theory is used to explain the correlation of the intensity of interpersonal communication of discipler – disciple and the interaction with groups in the churc with disciple’s interest to be actively involved as a member of ministry in GBI Gajah Mada Semarang church organization. The population of this study is the members of GBI Gajah Mada Semarang church involved discipleship. Sampling was done by the purposive sample of 40 respondents. The data analysis technique used Kendall rank correlation coefficient analysis. The hypothesis test showed the value of variable significance of the intensity of interpersonal communication of discipler – disciple (X1) and disciple’s interest to be actively involved as a member of ministry in church organization (X2) is 0.500, which is 0.500 > 0.05. In addition, the significant value of the variable the interaction with groups in the church (X2) and disciple’s interest to be actively involved as a member of ministry in church organization (Y) is 0.271, whic is 0.271 > 0.05. It means there is no correlation between the intensity of interpersonal communication of discipler – disciple and the interaction with groups in the church, and disciple’s interest to be actively involved as a member of ministry in church organization. In this research shows that external factors wich are the intensity of interpersonal communication of discipler – disciple and the interaction with groups in the church have no correlation with disciple’s interest to be actively involved as a member of ministry. It could be internal factors that have a correlation with the interest, there are motivations and expectations to be achieved from within disciple that may have a correlation with the disciple’s interest to be actively involved as a member of ministry in church organization.